Small jets in radio‐loud hot DOGs. Issue 1 (February 2016) - Lonsdale, C.J.; Whittle, M.; Trapp, A.; Patil, P.; Lonsdale, C.J.; Thorp, R.; Lacy, M.; Kimball, A. E.; Blain, A.; Jones, S.; Kim, M.
Abstract: We address the impact of young radio jets on the ISM and star formation in a sample of radiatively efficient, highly obscured, radio AGN with look back times that place them near the peak of the galaxy and BH building era, z ∼ 1–3. By selecting systems with a high mid‐infrared (MIR) luminosity we aim to identify radiatively efficient ("quasar‐mode" or "radiative‐mode") AGN in a peak fueling phase, and by selecting compact radio sources we favor young or re‐generated radio jets which are confined within the hosts. By selecting AGN which are very red through the optical‐MIR we favor highly obscured systems likely to have been recently merger‐triggered and still in the pre‐blow‐out phase of AGN feedback into the surrounding ISM. ALMA imaging at 345 GHz of 49 sources has revealed that they are accretion dominated, relative to star formation, with luminosities reaching 10 14 L⊙ . Extensive VLA imaging at 8–10 GHz in both A‐array and B‐array for 155 sources reveals that the majority of these powerful radio systems are compact on <2–5 kpc scales while some have resolved structures on 3–25 kpc scales, and a small number have giant radio lobes on hundreds of kpc scales. The majority of the GHz range radio SEDs are typical of optically thin synchrotron, however for the 34 sources with data at more than 2 frequencies, 40% are likely to be CSS, GPS, or HFP sources. VLBA imaging of 62 sources reveals varied morphologies, from unresolved sources to complex multicomponent 1–10 mas scale structures. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)